CPX-351 and allogeneic stem cell transplant for a therapy-related acute myeloid leukemia that developed after treatment of acute promyelocytic leukemia: a case report and review of the literature - Sperotto, Alessandra; Stanghellini, Maria Teresa Lupo; Peccatori, Jacopo; De Marchi, Roberta; Piemontese, Simona; Ciotti, Giulia; Basso, Marco; Pierdomenico, Elisabetta; Fiore, Paolo; Ciceri, Fabio; Gottardi, Michele (Frontiers in Oncology, 2024)
Therapy related myeloid neoplasms (t-MNs), developed after cytotoxic, radiation or immunosuppressive therapy for an unrelated disease, accounts for 7-8% of acute myeloid leukemia (AML). Worse outcome and consequently shortened survival are associated with t-MNs as compared with de novo AML. Therapy related MNs is being reported with increasing frequency in successfully treated acute promyelocytic leukemia (APL), in particular before the introduction of alltrans retinoic acid (ATRA) plus arsenic trioxide (ATO). Considering the high curability of APL, t-MNs represent one of the prognosis-limiting factors in this setting of leukemia. We report our experience in a patient who developed t-AML 15 years after treatment for APL. Treatment included three cycles of chemotherapy with CPX-351 (Vyxeos: Jazz Pharmaceuticals) followed, as in remission, by allogeneic hematopoietic stem cell transplant. A review of available literature was also included.